Mitochondrial fusion: Reaching the end of mitofusin’s tether - Formosa, Luke E. (J Cell Biol, 2016)
In this issue, Qi et al. (2016. J. Cell Biol. https://doi.org/10.1083/jcb.201609019) provide structural insights into the mechanisms of mitochondrial outer membrane fusion by investigating the structure of mitofusin 1 (MFN1). This work proposes a new model to explain the important and elusive process of MFN-mediated mitochondrial fusion.